To the inhabitants of the State of Vermont : Gentlemen, Whereas the General Assembly of this state did appoint me to wait on the Honorable Meshech Weare, Esq ; ... with a letter from his Excellency Thomas Chittenden, Esq ; and another from Col. Ethan Allen . - Allen, Ira, 1751-1814 ([Printed by J.P. & A. Spooner], 1778)
November 27, 1778 Letter from Ira Allen to the inhabitants of Vermont regarding New Hampshire's claim to sixteen towns east of the Connecticut River and the dispute with Vermont, as well as the meeting Allen had with the New Hampshire Council.